Triple-wavelength quantitative phase imaging with refractive index measurement. (September 2022) - Song, Jinwei; Min, Junwei; Yuan, Xun; Xue, Yuge; Bai, Chen; Yao, Baoli
Highlights: A method based on triple-wavelength quantitative phase imaging to quantitatively measure the refractive index (RI) and the topography of transparent samples is proposed. No needs of special highly dispersive medium, additional assistant technology and manual operation did anymore as the existed methods in the proposed method. The experimental configuration based on quadriwave lateral shearing interferometry (QLSI) is simple and compact, and has high stability. From the measured RIs, the composition of the sample can be identified besides the topography of the sample, and the proposed method is anticipated to be an effective and potential tool in RI and topography measurement of optical materials and identification of substance sort. Abstract: A method to quantitatively measure the refractive index (RI) and the topography of transparent samples is proposed. Three quantitative phase images at different wavelengths are firstly obtained by using a quadriwave lateral shearing interferometry (QLSI) technique, and then the RIs at the three wavelengths and the physical thickness distribution of the sample are independently calculated with the help of Cauchy's dispersion formula. Neither the highly dispersive medium nor the manual operation of changing the surrounding medium is required. From the measured RIs, the composition of the sample can be identified besides the topography of the sample. Both simulation and experimental results verified the effectiveness and feasibility of the proposed method.